Analisis Kepatuhan Wajib Pajak Bagi Pengendara Roda Dua di Kalangan Mahasiswa Kabupaten Sorong - Wanda, Rizky Febri; Fahmi, Fahmi (Multidisciplinary Journal of Education , Economic and Culture, 2025)
Tax on motorcyclists registered at the Sorong SAMSAT is known to have a lot of data on drivers who do not fulfill their obligations in paying motor vehicle tax. The purpose of this study was to determine the level of tax compliance at the student level, as well as to determine the factors that influence student compliance in paying taxes. The population used in this study were all two-wheeled motor vehicle taxpayers registered at the Sorong Regency SAMSAT office. The research method used in this study uses a qualitative research method to be able to understand the phenomenon in a natural social context that describes social problems in a person from a behavioral perspective. The results of this study indicate that taxpayer compliance is influenced by the way of thinking, tax knowledge, negligence, and of course taxpayer awareness. While external factors are influenced by tax access, quality of service, tax sanctions, and socialization by tax officers